The Unwillingness to travel to Bali during COVID-19 Pandemic: An Analysis of Negative Impact on Tourism and Risk Perception - Putu Gde Arie Yudhistira; Gusti Ayu Citra Arya Sucisanjiwani; Selvi Caroline Syaputra (Pusat Kajian Bali Universitas Udayana, 2022)
COVID-19 has spread widely throughout the world and was declared a pandemic that caused an impact on all industries, especially on tourism industry. This pandemic situation causes various negative impacts and risk perceptions that affect an individual's unwillingness to travel. This study aims to determine the effect of negative impacts and risk perception on the unwillingness to travel to Bali during COVID-19 pandemic. The research sample was 100 respondents. This research was quantitative research and used multiple linear regression analysis. The results were: (1) Negative Impact has a significant positive effect on Unwillingness to Travel, which the coefficient value is 0,672. (2) Risk Perception has a significant positive effect on Unwillingness to Travel, which the coefficient value is 0,043. (3) Negative Impact and Risk Perception simultaneously affect Unwillingness to Travel, which the constant value was 0,762. This research can be a consideration or reference for Bali tourism to minimize the negative impacts and risks of traveling to Bali during the COVID-19 pandemic.